PERAN FINTECH DALAM MENINGKATKAN KEUANGAN INKLUSIF PADA UMKM DI KABUPATEN SUMBAWA - Elly Karmeli; Ika Fitriyani; Rahmaningsih Febrianti (Jurnal Ekonomi & Bisnis, 2021)
This study aims to know the role of fintech in increasing financial inclusive of micro, small and medium enterprise (UMKM) actors in Sumbawa district.This study was descriptive qualitative.Sources of data used in this study were primary data and secondary data.Primary data in this study was data obtained directly from respondents through interviews while secondary data was supporting data from primary data.The method used to collect data in this study were through observation and interviews.The data analysis tool used was referred to the theory of Miles and Huberman which consists of 4 stages, namely data collection, data reduction, data presentation and conclusion drawing. The results of study showed that the impact of using fintech on UMKM in Sumbawa District had a positive effect in the development of Micro, Small and Medium Enterprises in Sumbawa District.The impact of using fintech in UMKM actors were payment transactions, capital financing, financial arrangements and sales promotions.